ANALISIS KINERJA KEUANGAN BANK BADAN USAHA MILIK NEGARA (BUMN) DENGAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL): (Studi Pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2014-2018) - Wulandari, Ayu; Taufiqurahman, Endang (JURISMA : Jurnal Riset Bisnis & Manajemen, 2021)
The global economy is currently experiencing a downturn, this has also affected the economies of several countries, including Indonesia. The effect of the downturn in the Indonesian economic sector has prompted Indonesian banks to improve the financial performance of their banks, as an effort to improve the Indonesian economy. This research was conducted with the aim of knowing how to calculate financial ratios, financial performance developments, and financial performance conditions in State-Owned Enterprises Banks. The research method used is descriptive quantitative. The data source used is secondary data. There are 4 population of companies that are registered as state-owned banks on the IDX, all of which have the requirements to be the sample of this study. Determination of the sample in this study using purposive sampling method. The analysis method used in this research is the RGEC (Risk Profile, Good Corporate Governance, Earning, Capital) method with financial ratios including the NPL (Non-Performing Loan) ratio, the LDR (Loan Deposite Ratio) ratio, ROA (Return On Asset), NIM. (Net Interest Margin), and CAR (Capital Adequacy Ratio). The results of this assessment show that the financial performance of state-owned banks listed on the IDX for the 2014-2018 period uses the RGEC method and has very good performance. Keywords: Financial Performance, RGEC Method, Risk Profile, Earning, Capital.